Formulation and Optimization of Immediate Release Tablets using Wet Granulation Method and Box-Behnken Design - Anjali Gupta; Vandana Mahawar; Shaily Chaudhary; Harish Kumar Tiwari; Vikas Patidar; Vishesh Bhaty; Yash Bairagi; Yashwant Choudhary; Aayushi Kushwaha; Akash Yadav (Revista Electronica de Veterinaria, 2025)
One of the most well-known over-the-counter medications is Paracetamol. Paracetamol is a Para-aminophenol derivative (N-acetyl-para-aminophenol) and has analgesic and antipyretic properties. The Paracetamol has high targeted action in the brain, it blocks an enzyme involved in Transmission of pain. Orphenadrine Citrate is one of the anticholinergic drugs that are used to treat painful muscle spasms, other similar conditions. It belongs to the ethanolamine category and antihistamine. Paracetamol is a BCS Class II drug having low solubility and high permeability and hence the basic objective was to produce immediate release tablets. Drug excipient interaction was investigated by placing vials containing drug excipient mixture at 45ºC±2ºC /75%±5% RH in wet and dry conditions which does not show any incompatibilities. The task of developing immediate release tablet is accomplished by varying the concentration of PVPK-30 and Sodium Starch Glycollate. Faster disintegration of the tablet administrated orally minimizes absorption time and improves its bioavailability in shorter period of time. The formulation development work was initiated with wet granulation method and a total of 4 formulations (A, B, C, D) were prepared. The formulated tablets were evaluated for various pre-compression and post-compression parameters. Tablets were found to be satisfactory when evaluated for thickness, weight uniformity, in-vitro drug release, assay, disintegration time. The in-vitro drug release for optimized formulation A was found to be 99.34% for Paracetamol and 98.81% for Orphenadrine Citrate at the end of 35 minutes and showed satisfactory (assay) drug content (98.75% Paracetamol & 97.86% Orphenadrine). The in-vitro drug release of optimized batch compared with marketed formulation and dissolution profile was found to be similar. From this study, it was concluded that optimized A batch containing PVPK-30 (8%) and Sodium Starch Glycollate (5%) showed better characteristics of immediate release tablets.